Electronic and Surface Properties of Aluminum (111) Surface Modified by Interstitial and Substitutional Titanium Incorporation - Irfan Dwi Aditya (Indonesian Journal of Physics, 2023)
This study investigates the influence of interstitial and substitutional titanium atoms on the electronic properties of aluminum surfaces using density functional theory (DFT). The study focuses on three variables: the presence and arrangement of Ti interstitials on the aluminum surface, the behavior of Ti substitutional and interstitial impurities, and the energetic stability and structural properties of these systems. Multiple DFT methods are employed to derive conclusions regarding the impact of these variables on the surface properties of aluminum. The study provides valuable insights into how different states of interstitial and substitutional Ti can alter the physical characteristics and performance behaviors of the aluminum surface. The understanding of these effects could enable engineers to design more efficient materials with enhanced properties suitable for various industries.